Electrochemical charge storage properties of novel inverse spinel (CuNiZnAlFe)3O4 type high entropy oxide - Gupta A.K.; Shubham K.; Giri N.K.; Shahi R.R. (My University, 2025)
The novel (CuNiZnAlFe)3O4 type nanocrystalline High Entropy Oxide (HEO) was synthesized through the sol-gel method with combustion at 350°C for 1 h duration. The XRD analysis reveals the formation of inverse spinel [B(AB)O4] type phase indexed with the space group of Fd-3 m confirmed through the Rietveld Refinement of the XRD data. The lattice constant for the synthesized spinel phase was found to be 8.2453°A. The Scanning Electron Microscope of the synthesized HEO confirms the flakes-like morphology with porous microstructure. The Energy Dispersive X-ray (EDX) analysis and elemental mapping confirm the homogeneous distribution of the cations over the selected region. It was found that Fe and Ni are in the +3 and +2 states, other cations, Cu and Zn, are in the +2 states, and Al is in the +3 confirmed through the X-ray photoelectron Spectroscopy. The electrochemical performance was studied in three electrodes in a 2 M KOH aqueous electrolyte. The specific capacitance value was 2.02, 1.58, 1.24, 1.06, 0.87, 0.71, and 0.65 F/g at scan rates of 5, 10, 20, 30, 50, 80, and 100 mV/s, respectively. The low value of specific capacitance was observed due to the stable ionic structure of the inverse spinel phase. The magnetization behavior of the sample is also investigated. The M-H loop of the (CuNiZnAlFe)3O4 HEO sample exhibits a ferrimagnetic nature. © 2023 John Wiley & Sons Ltd.